Transient hemiplegia in a child with Sturge-Weber/Klippel-Trenaunay syndrome - José Maria Pereira de Godoy MD, PhD*, Ana Carolina Pereira de Godoy, MD (Innovative Journal of Medical and Health Sciences, 2020)
This study was to describe the neurological evolution of a patient an association of Sturge-Weber and Klippel-Trenaunay syndromes. We report on a girl who was born with port wine-colored lesions over the entire body. The child later suffered two neurological episodes; the second left the patient hemiplegic, without consciousness and unable to speak. She started to recover after the seventh day, however full recovery took more than one month during which time periods of improvement and deterioration of cerebral perfusion were detected. Currently the patient is 23 years old, attended a college and is well without obvious neurological signs. Key words: Sturge-Weber syndrome–Klippel-Trenaunay syndrome–hemiplegia